2023
DOI: 10.1001/jamanetworkopen.2023.38315
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antepartum and Postpartum Air Pollution Exposure With Postpartum Depression in Southern California

Yi Sun,
Kathryne S. Headon,
Anqi Jiao
et al.

Abstract: ImportanceWomen are especially vulnerable to mental health matters post partum because of biological, emotional, and social changes during this period. However, epidemiologic evidence of an association between air pollution exposure and postpartum depression (PPD) is limited.ObjectiveTo examine the associations between antepartum and postpartum maternal air pollution exposure and PPD.Design, Setting, and ParticipantsThis retrospective cohort study used data from Kaiser Permanente Southern California (KPSC) ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Additionally, some PM 2.5 constituents and sources may be more harmful than others to health [34,35]. Previous studies found that different PM 2.5 constituents and exposure windows were differently associated with several adverse pregnancy outcomes, such as gestational diabetes mellitus [36] and postpartum depression [37], which is important to develop corresponding interventions targeting the main culprits and critical windows. However, very limited studies have investigated the windows of susceptibility to PM 2.5 and HDP risk [38], and the effects of PM 2.5 chemical compositions [12]; no prior study has explored the HDP risk related to overall mixture effects of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some PM 2.5 constituents and sources may be more harmful than others to health [34,35]. Previous studies found that different PM 2.5 constituents and exposure windows were differently associated with several adverse pregnancy outcomes, such as gestational diabetes mellitus [36] and postpartum depression [37], which is important to develop corresponding interventions targeting the main culprits and critical windows. However, very limited studies have investigated the windows of susceptibility to PM 2.5 and HDP risk [38], and the effects of PM 2.5 chemical compositions [12]; no prior study has explored the HDP risk related to overall mixture effects of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%